1986
DOI: 10.1159/000180556
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Somatomedin-C/Insulin-Like Growth Factor I by Nutrients

Abstract: Nutritional intake is an important regulator of plasma somatomedin-C/insulin-like growth factor I (Sm-C/IGF-I) concentrations in plasma. Concentrations in humans are reduced to the hypopituitary range by fasting for only a few days, and their normalization after fasting depends on the adequacy of energy and protein in the refeeding diet. The changes correlate with changes in nitrogen balance. In rats we have observed a close relationship between change in plasma Sm-C/IGF-I and hepatic GH binding with fasting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(45 citation statements)
references
References 15 publications
4
39
0
2
Order By: Relevance
“…This finding confirms that of several other groups in both animals and man (Underwood et al 1986, Vance et al 1992, Thissen et al 1994, Ohashi et al 1995. Not only is secretion of IGF-I reduced with fasting, but also synthesis is reduced as evidenced by falls in IGF-I mRNA (Zhang et al 1994, Kobayashi et al 1995.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding confirms that of several other groups in both animals and man (Underwood et al 1986, Vance et al 1992, Thissen et al 1994, Ohashi et al 1995. Not only is secretion of IGF-I reduced with fasting, but also synthesis is reduced as evidenced by falls in IGF-I mRNA (Zhang et al 1994, Kobayashi et al 1995.…”
Section: Discussionsupporting
confidence: 91%
“…IGF-I is also depressed (Underwood et al 1986, Vance et al 1992, Ohashi et al 1995 during fasting. It has been recently reported that impaired somatostatin distribution and release may also contribute to changes seen in the GH axis in nutritionally deprived animals (Aguila & McCann 1987, Sonntag et al 1995.…”
Section: Introductionmentioning
confidence: 94%
“…It is well established that increased total energy intake results in higher levels of IGF-I [29]. The lower IGFBP-1 in Sandwell Gujaratis is in keeping with lower insulin sensitivity (HOMA-S; Table 2), as we have described previously in other ethnic groups [15].…”
Section: Discussionsupporting
confidence: 77%
“…A Consensus Development Conference on Treatment of Destructive Behaviors in Persons with Developmental Disabilities will be held in Masur Auditorium in the Warren Grant Magnuson Clinical Center, National Institutes of Health, Bethesda, MD, September 1 [1][2][3][4][5][6][7][8][9][10][11][12][13]1989. This open forum will focus on the various treatments and approaches used to modify or eliminate destructive behaviors in persons with developmental disabilities.…”
Section: Announcementmentioning
confidence: 99%